2013
DOI: 10.1111/1556-4029.12264
|View full text |Cite
|
Sign up to set email alerts
|

Faith, Folie à Famille, and Mummification: A Brief Review of the Literature and a Rare Case Report

Abstract: Folie à deux is a rare clinical syndrome characterized by the transference of delusional ideas from one person to one or more other people in close association with the primary affected patient. Mummification indicates the preservation of the corpse of a person for a variable period of time. A brief review of the literature in this field is presented, and an exceptional case is described, characterized by the association of both these rare phenomena. The case is an example of folie à fammille which developed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
7
0
3
Order By: Relevance
“…Delírio persecutório é o tipo de delírio mais comumente encontrado nessa síndrome 3 , embora conteúdos religiosos possam estar presentes e dificultar a diferenciação de onde termina a fé e onde a psicose começa 2 . No entanto, o fenômeno descrito no caso gerou sofrimento, não foi compartilhado por outros, aconteceu fora de um contexto religioso, demonstrou-se fora de controle pelos envolvidos e não proporcionou crescimento pessoal.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Delírio persecutório é o tipo de delírio mais comumente encontrado nessa síndrome 3 , embora conteúdos religiosos possam estar presentes e dificultar a diferenciação de onde termina a fé e onde a psicose começa 2 . No entanto, o fenômeno descrito no caso gerou sofrimento, não foi compartilhado por outros, aconteceu fora de um contexto religioso, demonstrou-se fora de controle pelos envolvidos e não proporcionou crescimento pessoal.…”
Section: Discussionunclassified
“…Folie à deux, ou transtorno psicótico induzido, é uma síndrome rara 1 caracterizada por transferência de delírios de um sujeito considerado primariamente psicótico para um ou mais sujeitos considerados secundários em relação à origem do delírio 2 . Os sujeitos estão envolvidos em um contexto de relacionamento próximo, e classicamente em situações de confinamento 3 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…[65][66][67][68][69] It has been hypothesized that the genetic dispositions toward schizophrenia can also play an important role in the development of FaD, especially in the case of twins. [64][65][66][67][68][69][70][71] In addition, it has been reported that individuals who develop FaD have a high risk of schizophrenia in their families, with a very high prevalence of schizophrenia in firstdegree relatives (6.5%-26.2%), which is similar to the prevalence seen in first-degree relatives of schizophrenic patients (5.0%-16.9%). 21 Despite this evidence, the extent of genetic influence is difficult to determine.…”
Section: Risk and Etiological Factorsmentioning
confidence: 99%
“…One article describes the extraordinary case of 3 elderly, intensely religious sisters who developed a shared psychosis: folie à trois led to the horrible death of 2 of them, while the third sister lived for more than a year and a half with their mummified remains. 71 There are also cases of FaD associated with suicide pacts. 77,78 In these cases, the relations between the psychotic partners (domination-subordination) change over to relations of double suicide (instigator-participant).…”
Section: Forensic Aspectsmentioning
confidence: 99%